Optimization of Metakaolin-Based Alkali Activated Materials for Efficient Copper Removal from Wastewater - M. Ibrahim; W.M.W. Ibrahim; M.M. Al Bakri Abdullah; A. Romisuhani; P. Postawa; S. Ishak; R. Ediati (Archives of Metallurgy and Materials)
This study investigates the potential of metakaolin-based alkali-activated materials (AAM) as efficient adsorbents for copper removal through adsorption. The optimization process involved comparing the synthesis of AAM using metakaolin as the precursor material under two conditions: one with adding foaming agents, specifically hydrogen peroxide with a surfactant, and the other without any foaming agent. Characterization techniques, including specific surface area (BET), X-ray diffraction (XRD), and scanning electron microscopy (SEM), were employed to analyze the structural and morphological changes of the synthesized AAM. Batch adsorption experiments were conducted to evaluate the copper removal efficiency of the optimized AAM by considering factors such as initial copper concentration and pH. The Langmuir and Freundlich isotherm models were employed to investigate the adsorption mechanism and equilibrium behavior, providing insights into the adsorption process. The results demonstrated that the optimal AAM exhibited superior copper adsorption performance, achieving a removal efficiency of over 90% and best fitted with Langmuir isotherm suggesting that copper ions perform as a single molecule layer for MK-based AAM adsorption. This study contributes to the development of sustainable and effective materials for water treatment, particularly for addressing copper contamination. Metakaolin-based AAM with 1.00 wt.% hydrogen peroxide indicated the availability of numerous active sites for binding with Cu2+ and showed promise as a high-effective, convenient, and eco-friendly adsorbent for copper removal, with potential applications in various industrial and environmental settings.